Q. 2 A4.3( 16 Votes )

<span lang="EN-US

Answer :

In the given term


Dividend = (3x2– 2x)


Take out the common part in binomial term


= (3 × x × x– 2 × x)


= x(3x-2)


Divisor = x


=


= 3x-2


Hence dividing (3x2– 2x) by x gives out 3x-2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
NCERT | Factorisation ProblemsNCERT | Factorisation ProblemsNCERT | Factorisation Problems38 mins
Quiz | Questions on FactorizationQuiz | Questions on FactorizationQuiz | Questions on Factorization41 mins
Quiz | Important Questions on FactorisationQuiz | Important Questions on FactorisationQuiz | Important Questions on Factorisation35 mins
Algebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak Areas41 mins
Champ Quiz | Division of PolynomialsChamp Quiz | Division of PolynomialsChamp Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics